Essays in economic analysis : the proceedings of the Association of University Teachers of Economics, Sheffield, 1975 - Artis, Michael J.; Nobay, A. R.; Association of University Teachers of Economics (Cambridge, England ; New York : Cambridge University Press, 1976)
This volume brings together papers presented to the Conference of Association of University Teachers of Economics, held at Sheffield in April 1975. The volume displays the catholicity of interests of contemporary professional economists, and represents a cross section of the research undertaken at various universities, both in the United Kingdom and abroad.
Includes bibliographical references and index.
rpm 18/07/2017
Loans
Keywords: Economics